(untitled) (Italian Journal of Public Health, 2006)
The integration of genome-based information into public health is a challenging task. In this context, some emphasise a supposed fundamental difference of genome-based information compared to other health information. This view is contradicted by the author by arguing that genome-based information is determined by characteristics which also apply to other non-genome-based health information. Rather genome-based information integrates itself into the range of personal health information. Genome-based information deserves no “status apart” just because it was gained with the help of molecular diagnostic techniques. Thus there will be no revolution in public health, rather it can be discussed how genome-based information could be utilised to be part of public health approaches making public health more target-oriented and efficient.